2011
DOI: 10.1111/j.1365-2052.2010.02078.x
|View full text |Cite
|
Sign up to set email alerts
|

A new polymorphism in the Growth and Differentiation Factor 9 (GDF9) gene is associated with increased ovulation rate and prolificacy in homozygous sheep

Abstract: Brazilian Santa Inês (SI) sheep are very well-adapted to the tropical conditions of Brazil and are an important source of animal protein. A high rate of twin births was reported in some SI flocks. Growth and Differentiation Factor 9 (GDF9) and Bone Morphogenetic Protein 15 (BMP15) are the first two genes expressed by the oocyte to be associated with an increased ovulation rate in sheep. All GDF9 and BMP15 variants characterized, until now, present the same phenotype: the heterozygote ewes have an increased ovu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
14

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 27 publications
5
103
0
14
Order By: Relevance
“…Further, a mutation in GDF9 has been linked to increased ovulation rate when ewes are homozygous for the nonconservative change in an amino acid predicted to be involved in dimer formation. No change in ovulation rate was observed in heterozygous ewes (Silva et al 2011). This phenotype is similar to that described for the French Grivette sheep with mutations in BMP15.…”
Section: Gdf9 Mutationssupporting
confidence: 86%
“…Further, a mutation in GDF9 has been linked to increased ovulation rate when ewes are homozygous for the nonconservative change in an amino acid predicted to be involved in dimer formation. No change in ovulation rate was observed in heterozygous ewes (Silva et al 2011). This phenotype is similar to that described for the French Grivette sheep with mutations in BMP15.…”
Section: Gdf9 Mutationssupporting
confidence: 86%
“…Bone morphogenetic protein 15 (BMP15), growth differentiation factor 9 (GDF9), and bone morphogenetic protein receptor, type IB (BMPR1B), known as prolificacy candidate genes, play key roles in regulating ovarian functions in animals (Juengel et al 2002;Knight and Glister 2003 showed that ovulation rate in the heterozygotes was increased, but homozygous mutants were completely sterile (Galloway et al 2000;Hanrahan et al 2004;Bodin et al 2007;Martinez-Royo et al 2008;Monteagudo et al 2009). The mutations of GDF9 (FecG H , FecG T , FecG E , FecG F , and FecG V ) had introduced nonconservative amino acid changes reported to be associated with the litter size of sheep (Melo et al 2008;Nicol et al 2009;Silva et al 2011;Vage et al 2013;Souza et al 2014). A variation (FecB) in BMPR1B caused substitution of one amino acid (arginine to glutamine) and increased the ovulation rate of ewes (Mulsant et al 2001;Souza et al 2001;Fabre et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding studies carried out in Brazil on larger genes linked to prolificacy, a new single nucleotide polymorphism (SNP) located in the position 345 inside GDF-9 gene in the Santa Inês breed, that was named FecG E , may be related to the high ovulation frequency that is characteristic of this breed (Silva et al, 2010). No studies have been carried out investigating the FecX gene in the breeds analyzed here and no surveys have been noticed for this gene in any Brazilian breeds.…”
Section: Discussionmentioning
confidence: 91%
“…The Booroola mutation was found in the highlyconserved domain of intracellular serinetreonine-kinase of bone morphogenetic protein receptor 1B (BMPR-1B), characterized by a single change in nucleotides A to G (Q249R) resulting in a protein related with prolificacy phenotype in Merino-Booroola sheep (Mulsant et al, 2001, Souza et al, 2001, Wilson et al, 2001. The effect of this mutation, located in the autosomal chromosome 6, is addictive in the ovulatory rate.…”
mentioning
confidence: 99%